Driver factors of whistleblowing intention in undergraduate student perspective - Nadya Yunika Pratiwi; Bambang Minarso (Jurnal Inovasi Ekonomi, 2021)
This research aims to determine the factors that influence the intention of accounting students in Semarang city to as whistleblowers. The data source used is the primary data obtained using a questionnaire given to accounting students in Semarang City 2016 intake with proportionate stratified random sampling and taken is 314 respondents and processed data by multiple linear regression. The results showed that attitudes had no significant effect on intention whistleblowing, while subjective norms and perceived behavioral control significantly affected intention whistleblowing.